Primeira carta de Jeremias aos exilados: o desafio de viver sem templo e construir o shalom em terra estrangeira (uma análise de Jr 29,1-15) - Silva, Marisa Martins Furlan da (2021)
This research aims to analyze the first letter of Jeremiah sent to exiles in the sixth century VI BCE, recorded in Jr 29,1-15. The prophet’s exhortation aims to indicate a new way of life in Babylon that will be an effective (present) and apparently transgenerational (future) living space for the deported community. This material helps to understand this paradoxical relationship with the dominator, while revealing the controversy surrounding the activity of the prophet and his oracles. It is expected through this research, to identify if the deportees reached the challenges of living without a physical Temple and building the shalom in a foreign land, as an indication of a new moment for them.